What Attracts Tourists to Paradise? - Tsounta, Evridiki (Washington, D.C. : International Monetary Fund, 2008)
This paper investigates the determinants of tourism demand in the Eastern Caribbean Currency Union. We estimate the demand function in a panel setting using annual data from 1979 to 2005. Results show that tourism arrivals are significantly affected by economic developments in the source countries, while price considerations and external shocks (such as hurricanes and wars) are also important. Supply factors, such as developments in foreign direct investment and the number of airlines servicing a destination, are also found to be significant determinants of tourism demand.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet